2010
DOI: 10.1002/acr.20247
|View full text |Cite
|
Sign up to set email alerts
|

Do worsening knee radiographs mean greater chances of severe functional limitation?

Abstract: Objective. Development of functional limitation is thought to be unrelated to changes in severity of radiographic osteoarthritis (OA) of the knee. We evaluated the relationship of change in radiographic OA to the incidence of severe functional limitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 41 publications
(33 reference statements)
3
41
1
1
Order By: Relevance
“…Given the increase in gait disability with increased OA severity found in this study, patients with severe radiographic disease may be unable to easily execute activities of daily living such as ambulation, and they may also be unable to complete the physical activities prescribed as part of the treatment plan for their OA disease. As others studies have reported (Nebel et al, 2009;White et al, 2010;Wilson et al, 2011), the present study found that there was only a modest relationship between K/L grade and gait mechanics. Knee range of motion and peak vertical ground reaction force was inversely correlated with radiographic disease severity at both speeds.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Given the increase in gait disability with increased OA severity found in this study, patients with severe radiographic disease may be unable to easily execute activities of daily living such as ambulation, and they may also be unable to complete the physical activities prescribed as part of the treatment plan for their OA disease. As others studies have reported (Nebel et al, 2009;White et al, 2010;Wilson et al, 2011), the present study found that there was only a modest relationship between K/L grade and gait mechanics. Knee range of motion and peak vertical ground reaction force was inversely correlated with radiographic disease severity at both speeds.…”
Section: Discussionsupporting
confidence: 59%
“…The relationship between joint mechanics and radiographic disease severity is not yet fully understood. Some previous research has shown that radiographic OA correlates poorly with functional limitation (Summers et al, 1988), while other research has found that change in radiographic OA is related to the incidence of severe functional limitation (White et al, 2010). Nebel and colleagues found that radiographic disease severity accounted for as much as 18% of the variance in knee range of motion and 23% of the variance in peak vertical ground reaction force (Nebel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…White et al 38 reported a walking speed decrease of 4 cm/s over a 30-month period to be associated (relative risk, 1.8; 95% CI: 1.0, 3.3) with worsening radiographic OA in subjects who had a preferred gait velocity of 126 to 130 cm/s. The preferred gait velocity change of 7.9 cm/s seen in the cycling group in the current study exceeds these reported changes and is comparable to a previously reported minimal detectable change of 8 cm/s.…”
Section: Discussionmentioning
confidence: 99%
“…38 Minimal information has been published on walking speed and improvements in otherwise healthy and active subjects with knee OA. McDaniel et al 21 reported a gait speed of 99 cm/s in a group of subjects with a median knee OA severity of KL grade IV.…”
Section: Discussionmentioning
confidence: 99%
“…Yeni yapılan kesitsel bir çalışmada diz OA'sının kadın hastaların fonksiyonel durumlarını daha fazla etkilediği ve WOMAC skorlarının erkeklere oranla daha kötü olduğu bildirilmiştir (20). Otuz aylık takipli bir çalışmada radyografik diz OA'sında kötüleşme ile WOMAC fiziksel fonksiyon skorlarında bozulma arasında anlamlı bir ilişki bulunmuştur (21). Daha önce yapılan çalışmalarda WOMAC fiziksel fonksiyon alanının kuadriseps kas kuvveti ve dizde propriyosepsiyon bozukluğu ile ilişkili olduğu gösterilmiştir (15,22,23).…”
Section: Discussionunclassified